2020
DOI: 10.1542/peds.2019-1030
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Pediatric Residents: Three Years of National Survey Data

Abstract: BACKGROUND: We aimed to describe the national epidemiology of burnout in pediatric residents. METHODS: We conducted surveys of residents at 34 programs in 2016, 43 programs in 2017, and 49 programs in 2018. Survey items included the Maslach Burnout Inventory, demographics, program characteristics, personal qualities, experiences, and satisfaction with support, worklife balance, and learning environment. Analyses included cross-sectional comparisons and cross-sectional and longitudinal regression. RESULTS: More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 83 publications
3
65
1
1
Order By: Relevance
“…The data indicate that burnout is too common among pediatric residents to be the result of personal attributes. While there may be individual factors that impair or protect well-being [31], it is evident that systemic problems in residency training must be identified and addressed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data indicate that burnout is too common among pediatric residents to be the result of personal attributes. While there may be individual factors that impair or protect well-being [31], it is evident that systemic problems in residency training must be identified and addressed.…”
Section: Resultsmentioning
confidence: 99%
“…Generalization of results to all pediatric residency programs should be made with caution, but recent data from a multi-center cross-sectional study of pediatric residents surveyed annually during the 3 years of our study showed that burnout was prevalent amongst pediatric trainees nationwide [ 30 , 31 ]. Our program participated in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Recent literature suggests that rates of burnout in the pediatric trainee population are greater than 50% in each year of training and, not surprisingly, that burnout is associated with stress and sleepiness specifically, both of which may be affected by mindfulness practice. 11 For this reason, the American Association of Pediatrics aligned with the Accreditation Council for Graduate Medical Education in a 2014 statement that emphasized the need for systems-level change to address trainee burnout. 12 Mindfulness was the only evidence-based approach included in the statement that has been shown to reduce trainee burnout.…”
Section: Introductionmentioning
confidence: 99%
“…This anticipated and sought-after reward fosters a supportive community during training, potentially protecting against resident burnout. [2][3][4]…”
mentioning
confidence: 99%